Socioeconomic burden of hand, foot and mouth disease in children in Shanghai, China. (10th July 2015) - WANG, Z. L.; XIA, A. M.; LI, Y. F.; SU, H. L.; ZHAN, L. W.; CHEN, Y. P.; XI, Y.; ZHAO, L. F.; LIU, L. J.; XU, Z. Y.; ZENG, M.
SUMMARY: In the near future, the inactivated enterovirus 71 (EV71) vaccine is expected to become available on the market in China. Since EV71 is a major cause of hand, foot and mouth disease (HFMD), the vaccine is expected to significantly reduce the number of cases, as well as the detrimental economic effect of the disease. However, for a national vaccination strategy to be developed, policy-makers need more information on the socioeconomic burden of EV71 HFMD infection. Based on the 2011 population data, we estimated the clinical and economic effect of EV71 HFMD infection in children aged 0–9 years in Shanghai, China. The annual cost related to HFMD is >US$7.66 million for a population of 1·42 million children aged 0–9 years with an average cost of US$208.2/case. The extrapolated cost for EV71 HFMD infection was US$3.53 million, comprising 46·1% of the overall cost associated with HFMD. Around 97% of all of the HFMD-related expenses were paid for by the families creating a considerable economic burden. Our findings could provide the necessary recommendations on the most effective national EV71 vaccine implementation, as well as a baseline data for assessing the cost-effectiveness of the vaccine in China.